The role of TNF-α in the fate regulation and functional reprogramming of mesenchymal stem cells in an inflammatory microenvironment - Li, Weiqiang; Liu, Qianqian; Shi, Jinchao; Xu, Xiang; Xu, Jinyi (Frontiers in Immunology, 2023)
Mesenchymal stem cells (MSCs) are pluripotent stem cells with multidirectional differentiation potential and strong immunomodulatory capacity. MSCs have been widely used in the treatment of injured or inflamed tissues and immune-related diseases. Resting MSCs lack differentiation and immunomodulatory ability. Instead, they rely on microenvironmental factors to: 1) stimulate and regulate their expression of specific cell growth factors, chemokines, immunomodulatory factors or receptors; or 2) direct their differentiation into specific tissue cells, which ultimately perform tissue regeneration and repair and immunomodulatory functions. Tumor necrosis factor (TNF)-α is central to the creation of an inflammatory microenvironment. TNF-α regulates the fate and functional reprogramming of MSCs, either alone or in combination with a variety of other inflammatory factors. TNF-α can exert opposing effects on MSCs, from inducing MSC apoptosis to enhancing their anti-tumor capacity. In addition, the immunomodulation and osteogenic differentiation capacities of MSCs, as well as their exosomal microvesicle contents vary significantly with TNF-α concentration, time of administration, or its use in combination with other factors. Therefore, this review discusses the impact of TNF-α on the fate and functional reprogramming of MSCs in the inflammatory microenvironment, so as to provide new directions for improving the immunomodulatory and tissue repair functions of MSCs and enhance their therapeutic potential.